Soybean meal+milo, alfalfa hay, and dehydrated alfalfa pellets as protein sources for steers fed dormant, native tallgrass forage in drylot - T. DelCurto; R.C. Cochran; A.A. Beharka; E.S. Vanzant; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1989)
Sixteen ruminally-cannulated steers consuming dormant tallgrass-prairie forage were randomly assigned to one of four treatments: 1) control, no supplement; 2) soybean meal (SBM)+sorghum grain; 3) alfalfa hay; or 4) dehydrated alfalfa pellets. Forage dry matter (DM) intake was at least doubled by all three supplemental protein treatments (P.10) among treatments; however, fiber (NDF) digestibility was depressed in steers supplemented with SBM+sorghum grain or dehydrated alfalfa pellets, compared with controls. Results from this study reinforce the concept that supplemental protein improves forage intake and utilization. Additionally, alfalfa hay and dehydrated alfalfa pellets appear to be at least as effective as SBM+sorghum grain when fed on an equal protein and energy basis.
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Soybean meal; Milo; Alfalfa hay; Dehydrated alfalfa pellets; Protein; Steers; Tallgrass forage